2013
DOI: 10.1074/jbc.m113.486878
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with Cfd1 Increases the Kinetic Lability of FeS on the Nbp35 Scaffold

Abstract: Background: A Cfd1 and Nbp35 heterocomplex serves as scaffold for cytosolic iron-sulfur cluster assembly. Results: Deficiency in Cfd1-Nbp35 interaction impaired iron turnover on Nbp35. Conclusion: Cfd1 promotes binding and transfer of labile iron-sulfur cluster on the Nbp35 scaffold. Significance: This is the first insight into the unique roles of these P-loop ATPases in cytosolic iron-sulfur cluster assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 39 publications
1
45
0
Order By: Relevance
“…This observation suggests that the Nbp35-Cfd1 complex is not in rapid equilibrium with the Nbp35 and Cfd1 homocomplexes. This observation is in agreement with the recent report that differentially epitope-tagged Nbp35 and Cfd1 subunits separately expressed in yeast do not reorganize to form an Nbp35-Cfd1 complex in yeast cell-free extracts (24).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This observation suggests that the Nbp35-Cfd1 complex is not in rapid equilibrium with the Nbp35 and Cfd1 homocomplexes. This observation is in agreement with the recent report that differentially epitope-tagged Nbp35 and Cfd1 subunits separately expressed in yeast do not reorganize to form an Nbp35-Cfd1 complex in yeast cell-free extracts (24).…”
Section: Resultssupporting
confidence: 82%
“…Nbp35 and Cfd1 are both required for the biosynthesis of FeS clusters in the cytosol. Although it is well known that these proteins can form a heterocomplex in vitro and in vivo (7,8,12), recent work utilizing overexpressed, epitope-tagged constructs of Nbp35 and Cfd1 demonstrated that up to 60% of the Nbp35 and Cfd1 polypeptides form homocomplexes in yeast (24). It remains to be established what if any differing functional roles the Nbp35 and Cfd1 homocomplexes and the heterocomplex play in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Based on currently available knowledge, Cfd1-Nbp35 could be the first interaction partners of X-S. Further, the NADPH-dependent electron transfer chain composed of the diflavin reductase Tah18 and the Fe/S protein Dre2 is required, in particular for generation of the N-terminal [4Fe-4S] cluster of Nbp35 (Netz et al, 2010;Zhang et al, 2008). This cluster is bound in a stable fashion yet its function is unknown (Pallesen et al, 2013). Dre2 is believed to bind a [2Fe-2S] and a [4Fe-4S] cluster.…”
Section: How the Cia Machinery Uses The Exported Atm1 Substrate For Fmentioning
confidence: 98%
“…The initial step of cytosolic Fe/S protein assembly is the synthesis of a transiently bound [4Fe-4S] cluster on the hetero-tetrameric scaffold complex of Cfd1-Nbp35 (Hausmann et al, 2005;Netz et al, 2012a;Netz et al, 2007;Pallesen et al, 2013;Roy et al, 2003) (Fig. 3).…”
Section: How the Cia Machinery Uses The Exported Atm1 Substrate For Fmentioning
confidence: 99%
“…The electron from Dre2 could be used to reduce the GSH carrier to its free form to facilitate delivery of S-X to Nbp35/Cfd1. The structural mechanism of this process remains unclear as in vitro experiments show that both Cdf1 and Nbp35 can individually coordinate and transfer clusters to apoproteins in the presence of free iron and sulfur without nucleotide binding or complex formation [203,206]. Plants and bacteria do not have Cfd1 but instead bind four [4Fe-4S] clusters as a homodimer, while Cdf1 in non-photosynthetic eukaryotes has been shown in vivo and in vitro to increase liability and transfer of Fe-S clusters to target apoproteins [206,207].…”
Section: Dna Processing Enzymes Share Common Fe-s Cluster Maturatimentioning
confidence: 99%